Studies in Teaching: 2019 Research Digest - (:unkn) unknown (Wake Forest University, 2025)
This document presents the proceedings of the 24th Annual Research Forum held June 27, 2019, at Wake Forest University in Winston-Salem, North Carolina. Included are the following eleven action research papers: (1) How Does Student Goal Setting Affect Motivation to Learn? (Wendell Dunn); (2) Combatting Confirmation Bias: How Writing from Opposing Perspectives Affects Understanding of Issues (Philip Grossenbacher); (3) Impact of Primary Source Activities on Student Understanding, Engagement, and Interest (Ella Wren Hill); (4) The Effect of Reading Aligned Children's Literature in Kindergarten Mathematics (Rachel Hirsch); (5) Making History Matter: How Current Event News Articles Influence Student Connections to History (Ryan Julian); (6) The Effect of Student-Produced Performative Film on Attitude toward Learning (William Kaskay); (7) Argumentative Activities and Reasoning in Elementary Mathematics (Hannah Maness); (8) The Effects of Inquiry Tasks on Students' Conceptual Understanding and Attitudes (Melissa McGahan); (9) How the Practice of Intercultural Pedagogy Impacts Cultural Intelligence among Students (Dana Reddick Nicholson); (10) Demonstration of Scientific Mindset in Secondary Students through an Independent Research Project (Samantha Stangl); and (11) Effects of Adapted Primary Literature Use on Scientific Literacy (Rachel Walter). Individual papers contain references, tables, and figures. [For the 2018 Research Digest, see ED586326.]
Action Research Projects Presented at the 24th Annual Graduate Student Research Forum
Keywords: Abstract Reasoning; Bias; Childrens Literature; Cultural Awareness; Current Events; Elementary School Mathematics; Film Production; Goal Orientation; History Instruction; Inquiry; Instructional Materials; Kindergarten; Learner Engagement; Learning Motivation; Multicultural Education; News Reporting; Perspective Taking; Primary Sources; Research Projects; Scientific Literacy; Secondary School Students; Student Attitudes; Student Interests; Thinking Skills; Writing (Composition)